Pencapaian Dimensi Ketakwaan dan Bernalar Kritis Siswa dengan STEAMRel-PBL Dilengkapi E- Authentic Assessment pada Pembelajaran Ekologi - Setiowati, Wiwin; Hariyadi, Slamet; Prihandono, Trapsilo (Biosfer: Jurnal Pendidikan Biologi, 2025)
The STEAMRel-PBL learning model equipped with authentic e-assessment is used in ecology and biodiversity learning to determine its influence on critical reasoning skills and the achievement of aspects of piety, especially students' morals towards nature. This study aims to determine the effectiveness of the STEAMRel-PBL learning model equipped with authentic e-assessment on the achievement of students' attitude of piety, especially their morals towards nature and their ability to reason critically in ecological learning. The research design carried out was a quasi-experiment of one pretest-post-test group. The research involved 30 grade VII students. Data collection techniques were carried out using pretest-post-test instruments, interviews, observations, and questionnaires. Data analysis was carried out using the N-Gain formula and calculation with a Likert scale. The results showed that the N-Gain value score showed that the STEAMRel-PBL model equipped with authentic e-assessment demonstrates significant influence in the development of students' critical reasoning. All critical reasoning indicators are on the criteria of developing as expected. The dimension of faith in fear of God Almighty is assessed using a questionnaire instrument that contains moral indicators towards nature. The results of the moral assessment of students are in the criteria of developing according to expectations, with the average student achievement being 86.88. Religious values help students reflect on God's role in His creation through science, which further strengthens their piety.